2018
DOI: 10.1080/15320383.2018.1506425
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of oil-particle aggregate (OPA)-containing sediments

Abstract: Sediments composed of oil-particle aggregates (OPAs) have unique physical characteristics. These in situ deposited sediments develop at locations where a continual or nearly continual discharge of nonaqueous phase liquids (NAPLs) have occurred, or are occurring through time. The NAPL discharged into the surface water body interacts with suspended particles in the water column. The particles adhere to the suspended NAPL, which generally is in the form of a bead, and produce a discrete aggregate. As the aggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…Previous studies (Johnson et al, 2018) of these sediments indicate indicated the IDN sediments consist of an open porous structure composed primarily of submicron size pores. The majority of the fluids within the pore network are retained within these small pores.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Previous studies (Johnson et al, 2018) of these sediments indicate indicated the IDN sediments consist of an open porous structure composed primarily of submicron size pores. The majority of the fluids within the pore network are retained within these small pores.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast to upland-based soils, the pore network of IDN sediments is more open, as reflected by higher porosity values. IDN sediment porosity values typically range from 50% to 80% (Johnson et al, 2018). The higher porosity reflects the deposition of the particles from the surface water and the absence of any significant compaction.…”
Section: Napl Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suspended particulate matter and aggregates of detritus, living organisms and inorganic matter known as marine snow, play an important role through the adsorption of hydrocarbons and the association of dispersed oil droplets Passow and Ziervogel 2016). The particles less than 2 μm with the capacity to bind hydrophobic compounds dominate free surface of natural waters, leading to a significant amount of oil sedimentation via agglomeration (Johnson et al 2018). 87-98% of spilled oil may change to ''particulate'' form, either incorporated into suspended particulate matter aggregates or as particulate free oil globules (Johnson et al 2018).…”
Section: Table Of Figuresmentioning
confidence: 99%
“…The particles less than 2 μm with the capacity to bind hydrophobic compounds dominate free surface of natural waters, leading to a significant amount of oil sedimentation via agglomeration (Johnson et al 2018). 87-98% of spilled oil may change to ''particulate'' form, either incorporated into suspended particulate matter aggregates or as particulate free oil globules (Johnson et al 2018).…”
Section: Table Of Figuresmentioning
confidence: 99%